2000
DOI: 10.1038/sj.bmt.1702129
|View full text |Cite
|
Sign up to set email alerts
|

Sequential vidarabine infusion in the treatment of polyoma virus-associated acute haemorrhagic cystitis late after allogeneic bone marrow transplantation

Abstract: Summary:Late onset haemorrhagic cystitis (HC) occurs in 20-30% of allogeneic bone marrow transplant patients. Human polyomavirus BK (BKV) (or less frequently adenovirus) may be involved in the pathogenesis of viral HC and can represent a serious post-transplant complication. Diagnosis and treatment of viral HC can be difficult and has an uncertain outcome. We report the efficacy of sequential vidarabine in the treatment of a patient with severe BKV-associated HC, despite the delay in implementing therapy. Bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…As some viruses are detected in blood and urine samples in LOHC, the administration of antiviral agents has been much tried in recent years, including vidarabine, 14 ribavirin, 15 ganciclovir 16 or cidofovir; 17 however, it is rather difficult for the specific choice of antiviral agents to any HC patient. Ganciclovir prophylaxis is thought to be effective when given to all CMV-positive patients or to patients who were considered at high risk for CMV disease on the basis of a positive surveillance culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As some viruses are detected in blood and urine samples in LOHC, the administration of antiviral agents has been much tried in recent years, including vidarabine, 14 ribavirin, 15 ganciclovir 16 or cidofovir; 17 however, it is rather difficult for the specific choice of antiviral agents to any HC patient. Ganciclovir prophylaxis is thought to be effective when given to all CMV-positive patients or to patients who were considered at high risk for CMV disease on the basis of a positive surveillance culture.…”
Section: Discussionmentioning
confidence: 99%
“…2,13 Encouraging results with antiviral agents have been published; however, there is no evident proof in a large number of patients and mainly improve clinical symptoms. [14][15][16][17] The use of formalin, alum, prostaglandin E1, estrogens, FVIIa, factor XIII, hyperbaric oxygen treatment, intravesicular sodium hyaluronate, recombinant human epidermal growth factor or recombinant human GM-CSF has been described, but their efficacy remains controversial. [18][19][20][21][22][23][24][25][26][27] Severe HC may also require surgical treatment with cystoscopy and cauterization, and even cystectomy when previous methods have failed, 28 but it is limited by the disadvantage of operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, BK virus could still be detected in the urine after recovery as has been reported in the literature. [3][4][5] In both cases, GVHD preceded the HC and the immunosuppressive therapy could have had a role in the reactivation of both viruses. GVHD is considered a risk factor for the development of HC by several authors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that reactivation of the BK polyomavirus is an important pathogen in the development of HC post BMT. [2][3][4][5] An association between reactivation of CMV and late-onset BK virus-associated HC was recently described in recipients of allogeneic BMT 8 and a trend towards a higher incidence of HC in patients with reactivation of CMV was described in T celldepleted BMT recipients. 7 BK virus and JC virus are members of the human polyomaviruses, and each is 70% homologous with the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation